Effects of Systemic Simvastatin on the Concentrations of Visfatin, Tumor Necrosis Factor-α, and Interleukin-6 in Gingival Crevicular Fluid in Patients with Type 2 Diabetes and Chronic Periodontitis - Maha A. Bahammam; Mai S. Attia (Journal of Immunology Research)
Purpose. The objective of this study is to explore the relationship between the levels of interleukin- (IL-) 6, tumor necrosis factor- (TNF-) α, and visfatin and simvastatin usage, in the gingival crevicular fluids (GCFs) of diabetic patients afflicted with chronic periodontitis. Methods. Eighty outpatients at the Periodontology Department, Faculty of Dentistry, University Dental Hospital (King Abdulaziz University), were categorized into 4 groups (20 patients per group), on the basis of radiological evaluation of bone loss, clinical attachment levels (CAL), probing depth (PD), and gingival indices: group 1 (healthy periodontium), group 2 (chronic periodontitis + type 2 diabetes), group 3 (chronic periodontitis), and group 4 (type 2 diabetes + chronic periodontitis + simvastatin). Enzyme-linked immunosorbent assays were used to measure IL-6, TNF-α, and visfatin levels. Results. Significantly elevated levels of IL-6, TNF-α, and visfatin were seen in group 2 in comparison to groups 1 and 3. Reduced levels were seen in group 4 due to simvastatin usage. Positive association was seen between periodontal variables and the levels of IL-6, TNF-α, and visfatin. Conclusion. Periodontal destruction and diabetes have a synergistic effect on the elevation of inflammatory cytokine levels. Simvastatin may be beneficial in improving periodontal health among diabetic patients.